2017
DOI: 10.1089/thy.2017.0383
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction is Common in Survivors of Pediatric Differentiated Thyroid Carcinoma

Abstract: While systolic function is unaffected, diastolic dysfunction is frequently observed in asymptomatic long-term survivors of pediatric DTC, which may suggest early cardiac aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Morbidity caused by treatment remains substantial, however, mainly as a consequence of surgical complications (permanent hypoparathyroidism and recurrent laryngeal nerve injury present in up to 32%) (18). Other late effects of childhood DTC treatment include dry mouth (19) or dry eyes that may have been caused by 131 I¯ treatment or side effects induced by TSH suppression therapy, such as altered diastolic function (20). Awareness of these late effects of given treatment in childhood is important.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity caused by treatment remains substantial, however, mainly as a consequence of surgical complications (permanent hypoparathyroidism and recurrent laryngeal nerve injury present in up to 32%) (18). Other late effects of childhood DTC treatment include dry mouth (19) or dry eyes that may have been caused by 131 I¯ treatment or side effects induced by TSH suppression therapy, such as altered diastolic function (20). Awareness of these late effects of given treatment in childhood is important.…”
Section: Discussionmentioning
confidence: 99%
“…Increased CVD morbidity and mortality have been reported among well-differentiated thyroid carcinoma patients, and THST was considered as a major cause of the cardiovascular problems [7,[10][11][12][13][14][15][16][17][18][19][20][21]. Klein Hesselink et al reported that a lower TSH level is associated with increased CVD mortality in thyroid cancer patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…Hummel et al demonstrated subtle LV systolic and diastolic dysfunction, despite unchanged EF, at a median of 21.7 years follow-up in a small group of survivors of head and neck cancer treated with cranial and neck radiotherapy without additional systemic therapy, however the radiation dose was considerably higher in this group compared to CRT dose in ALL [35]. Furthermore, data from pediatric differentiated thyroid carcinoma survivors suggest that consequences of treatment with thyroidectomy and radioiodine may as well have delayed effects on the heart, including subclinical LV dysfunction [36].…”
Section: Discussionmentioning
confidence: 99%